Diseño de un Prototipo Hidráulico de Baja Potencia para la Generación de Energía en la Sierra Nevada de Santa Marta (2021)
Abstract This research is oriented towards supporting and caring for the environment, with the use of clean energies and in search of continuous improvement to meet the needs that humanity has at this time. Colombia for being one of the richest countries in terms of water sources or with the largest number of rivers, it is intended to implement the development of ideas where a positive impact is generated without compromising natural resources. So then, in recent years with the advancement of energy production through hydraulic energy, at a very low cost, thanks to the movement of water, this will help us solve this problem by generating environmental benefits and satisfying the needs of human beings.